Implementasi Mesin Pencacah Pakan Ternak Portabel dalam Program KKN untuk Mendukung Produktivitas Peternak Desa Aek Korsik, Kabupaten Asahan - Nur Esa Fahrizar; Nini Dea Mirabel; Khairul Saleh (STIKes Ibnu Sina Ajibarang, 2025)
Livestock production in rural communities relies heavily on the availability and quality of animal feed. In Aek Korsik Village, Asahan Regency, farmers continue to use manual methods to chop forage, which are time-consuming, inconsistent, and physically demanding. To address these issues, a portable forage chopper machine was designed and introduced through a community service program (KKN). The machine features a compact mechanical system powered by a small motor, making it lightweight, mobile, and easy to operate in various conditions. The implementation process included three stages: machine development, field testing, and community training. During testing, the machine efficiently processed forage materials like grass, corn stalks, and agricultural residues, producing uniform feed sizes much faster than manual methods. Farmers reported reduced workload, improved availability of chopped forage, and better livestock feeding practices. The portable design allowed the equipment to be shared among farming groups, fostering cooperation. This study underscores the role of appropriate technology in addressing rural agricultural challenges. By integrating engineering innovation with community service, the portable forage chopper machine enhances technical efficiency and socio-economic empowerment for farmers. Future improvements should focus on durability, cutting capacity, and sustainable energy alternatives to better meet the needs of smallholder farmers.